The Desirable Features of Content in Higher Education with an Emphasis on the Lifelong Learning Approach: A Qualitative Research - Mitra Kamyabi (Strides in Development of Medical Education, 2022)
Background: Nowadays, expectations from higher education systems have changed, and the purpose of these centers is not only to transfer information. One of the solutions to respond to higher education’s new need is to move toward lifelong learning.Objectives: This research was conducted to investigate the desirable features of content in higher education with an emphasis on the lifelong learning approach.Methods: This qualitative study was conducted with a content analysis approach in 2019. Nineteen faculty members of Isfahan University, Shahid Bahonar University of Kerman, and Medical Sciences Universities of Kerman and Isfahan, who were experienced in the fields of curriculum planning, higher education, and teaching and learning, were selected to participate in the study through purposive sampling. Data were collected through open-ended semi-structured interviews. Graneheim and Lundman’s qualitative method was used to analyze the data. The results of data analysis were presented during three stages of open, axial, and selective coding. The peer check method and external observer were used in order to ensure the reliability and acceptability of the data.Results: According to the results of this research, three main categories were identified as the desirable features of content with an emphasis on the lifelong approach. The first category was “suitability of the content for society and its needs”, which includes the components of being up-to-date and applicability and usefulness. The second category is “suitability for the learner and his/her needs”, which includes the dimensions of matching with the learner’s interest, need, and ability, developing individual skills according to the learners’ potential, and developing excellent thinking skills. The third category is “suitability for curriculum regulations”, which includes the components of continuous education, learning with multiple methods, quality, flexibility, diversity, coherence, and self-direction.Conclusion: The results of this research can be used in revising higher education content with an emphasis on educating individuals with the feature of lifelong learning.